Study of interstrip gap effects and efficiency for full energy detection of Double Sided Silicon Strip Detectors. (March 2015) - Torresi, D; Forneris, J; Grassi, L; Acosta, L; Di Pietro, A; Figuera, P; Grilj, L; Jaksić, M; Lattuada, M; Mijatović, T; Milin, M; Prepolec, L; et al.
Abstract: In this work is reported a study on the response of double sided silicon strip detectors. In order to investigate the effect of the electrode segmentation on the detector response, two experiments were performed aimed to measure the efficiency for full energy detection. Results show that the efficiency for full energy detection, that is directly related to effective width of the inter-strip region, varies with both detected ion energy and bias voltage. The experimental results are qualitatively reproduced by a simplified model based on the Shockley-Ramo-Gunn framework.